Organisasi Pemerintahan Kerajaan Mataram Islam Pada Masa Sultan Agung (1613-1645 M) - Zaid Munawar, Zaid Munawar (Sekolah Tinggi Agama Islam Program Studi Sejarah dan Kebudayaan Islam, 2025)
This study aims to examine how Sultan Agung organized the government throughout the territory of the Islamic Mataram Kingdom and how the organizational/bureaucratic structure was formed to create a controlled government both at the central and regional levels. This study is a qualitative study using a library study approach. Data were collected from various literature such as books, journals, and reports. The results of the study indicate that Sultan Agung organized the government based on the concept of state territory centered in the palace and expanding outward. The territory of power was divided into four parts with officials within it to create a controlled government both at the central and regional levels, namely 1) Kutagara, there were officials such as patih, under the wedana, and assisted by a kliwon, kebayan, and 40 mantri jajar; 2) Negara Agung, there were officials such as patih-jawi, under the wedana-jawi, and assisted by a demang; 3) Mancanegara, there was a regent with the title Tumenggung/Raden Arya; 4) Pasisiran, there was also a regent known as Syahbandar. In addition to the high-ranking central officials, there were also approximately 150 other lower-ranking officials, specialized in various fields. All of these positions constituted a traditional bureaucracy, serving as an extension of the royal household, acting on the king's orders and receiving rewards as royal favors, which could be withdrawn at any time, as all officials were required to serve the king.